MATHEMATICAL MODELING OF HEAT-EXCHANGE PROCESSES IN FUEL HEATING FURNACES OF CHAMBER-TYPE - I. A. Trusova; P. E. Ratnikov; D. V. Mendelev; S. V. Korneev (Литьë и металлургия)
The solving of problem of structural identification of the mathematical model of heat exchange in chamber reheating furnace is presented.